Volatile composition analysis of five different Commiphora mukul (Hook. ex Stocks) Engl. gum samples - Sanam Varamini; Amirhossein Sakhteman; Gholamhosein Yousefi; Masoud Sepehri; Pouya Faridi; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2016)
Commiphora mukul (Hook. ex Stocks) Engl. (from the family Burseraceae) is well known the clinical applications of related gummy compositions. The gum possesses many pharmacological activities such as antiseptic, astringent, anti-inflammatory and antimicrobial activities. To outline a frame from chemical compositions of this medicament, current study has evaluated the essential oil extracted from different C. mukul gum samples found in medicinal plants markets in Iran. Five different Samples were purchased from medicinal plants market in Shiraz and were coarsely milled and subjected to a Clevenger-based hydrodistillation. Subsequently GC/MS analysis was performed for each sample by means of a gas chromatograph (Agilent Technologies 7890) coupled with a mass detector (Agilent Technologies model 5975C). Identification of the constituents was performed based on a comparison of their mass spectra with Willey (nl7) and Adams libraries spectra, as well as with those reported in literatures. The yield of extracted colorless but turbid essential oil from those samples was calculated at the range of 0.5-1% (V/W). Totally, 41 different components were identified for those collected samples. Major constituent (more than 5%) found in all samples was Alpha-Cadinol (7.25-14.49%). Results of the current procedure can be considered as a reference for the analysis and control of different C. mukul samples from markets.